Codification hubs of the Hungarian prison affairs (Academic Journal of Internal Affairs, 2020)
A sophisticated and in its sense unique topic elaborating monograph was issued by the publisher Dialóg Campus Kiadó making available the comprehensive historical-legal work of József Palló „Codification hubs of the Hungarian prison affairs”. The author makes lesser-known previous history of punishment law as a relative law sector known with background knowledge, not free of adversity, of the codification attempts and results in the 19th and 20th century. This great assignment is approximated especially sensitively, disclosing until now not known depths and besides expressive announcement of the legal policy affecting codification processes quoting and presenting for the readers even opinions and arguments of contemporary specialised literature in an analysing-evaluating perspective.
Keywords: book review; prison affairs; punishment law